2013
DOI: 10.1108/itp-10-2012-0116
|View full text |Cite
|
Sign up to set email alerts
|

Don't give up the community: a viewpoint of trust development in online collaboration

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 44 publications
2
18
1
2
Order By: Relevance
“…To measure an individual's performance, all students were required to complete a questionnaire three times during the project period to value their trust level from the six trust factors we selected (Cheng, Nolan and Macaulay, 2013). We also conducted interviews with each of the students.…”
Section: Case Studymentioning
confidence: 99%
“…To measure an individual's performance, all students were required to complete a questionnaire three times during the project period to value their trust level from the six trust factors we selected (Cheng, Nolan and Macaulay, 2013). We also conducted interviews with each of the students.…”
Section: Case Studymentioning
confidence: 99%
“…In our case study, we found that thinkLets can also improve the satisfaction of the learning design. For example, thinkLets can reduce distraction within the discussion which is an important issue in group learning (Cheng et al , ). One student said that “ With the help of the thinkLets process, we could also save a lot of time and reduce deviation from the topic at hand .” To sum up, thinkLets can help students to reduce distractions, get consensus quickly and create more ideas.…”
Section: Resultsmentioning
confidence: 99%
“…Some scholars in the CE field have mentioned that some factors are important when applying the CE method, and could be considered as influencing factors, such as low participation (Cheng et al , ; McFadzean & McKenzie, ), distraction (Briggs et al , ; Davison & Briggs, ) and inefficiency (Minnaert et al , ). Understanding influencing factors, especially their relationships, will help future CE design and improvement.…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of the questionnaires was based on the Trust Evaluation Survey of prior study [53] about trust and trust factors in computer mediated collaboration. In our research, we selected all questions of the Trust Evaluation Survey from the perspective of risk, benefit and interest, in addition, we added three questions about individual trust.…”
Section: Surveymentioning
confidence: 99%